1997
DOI: 10.1176/ajp.154.10.1376
|View full text |Cite
|
Sign up to set email alerts
|

Depression in medically ill hospitalized older adults: prevalence, characteristics, and course of symptoms according to six diagnostic schemes

Abstract: Objective: The purpose of this study was to examine and compare rates of depression, correlates, and course of symptoms in medically ill hospitalized elders through use of six diagnostic schemes (inclusive, etiologic, exclusive-inclusive, exclusive-etiologic, substitutiveinclusive, and substitutive-etiologic 1997; 154:1376-1383)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Others have suggested that traditional symptoms scales or diagnostic assessments may under-represent depression in older adults who may more often present with somatic symptoms or cognitive complaints (29). Alternatively, older adults' more frequent contact with health care may result in a higher likelihood that less severe depression will be recognized and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that traditional symptoms scales or diagnostic assessments may under-represent depression in older adults who may more often present with somatic symptoms or cognitive complaints (29). Alternatively, older adults' more frequent contact with health care may result in a higher likelihood that less severe depression will be recognized and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility came from our diagnostic approach in consultation. As depressive symptoms and medical illness interact bidirectionally, we adopted the inclusive approach, which was to include those depressive symptoms even when physical illness might be related to the symptoms [47]. Thus, in the diagnosis of major depression, especially for the current episode, this inclusive approach tended to over-diagnose and might possibly include those of adjustment disorder or demoralization [48].…”
Section: Discussionmentioning
confidence: 99%
“…These data seem to suggest that a simplified list of symptoms may be considered, at least for use in people with comorbid physical illness. However, an investigation conducted in medically ill hospitalized elders [32] found that a diagnostic approach omitting somatic symptoms led to the exclusion of a large proportion of patients who continued to experience persistent symptoms of depression many weeks after discharge.…”
Section: Validation Of the Concept Of Major Depressionmentioning
confidence: 99%